Educational and Cultural Diversity from an Islamic and Kuantan Malay Perspective - Respito Rini; Nur Isdianti; Melda Rahmatul karima; Irfandi (Penerbit Hellow Pustaka, 2024)
This research explores the diversity of education and culture from the perspective of Islam and Kuantan Malay society, with a focus on how Islamic Education traditions and values influence and enrich cultural life. The Kuantan Malay community has a rich and diverse cultural heritage, where local traditions such as reading the book Al-Barzanji, village martial arts and grave pilgrimage culture play an important role in education and daily life. This research seeks to explain the diversity of education and culture in Jaya Kopah Village, Central Kuantan District, Kuantan Singingi Regency. The research method used is a qualitative research method. It is hoped that the results of this research will make an important contribution in understanding the dynamics of culture and education in Kuantan Malay society, as well as its relevance in a broader context.